2019
DOI: 10.1177/1071181319631121
|View full text |Cite
|
Sign up to set email alerts
|

Automated Speech Recognition Systems and Older Adults: A Literature Review and Synthesis

Abstract: The number of older adults is growing significantly worldwide. At the same time, technological developments are rapidly evolving, and older populations are expected to interact more frequently with such sophisticated systems. Automated speech recognition (ASR) systems is an example of one technology that is increasingly present in daily life. However, age-related physical changes may alter speech production and limit the effectiveness of ASR systems for older individuals. The goal of this paper was to summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…However, age-related physical changes may alter speech production and limit the effectiveness of ASR systems for older individuals. Evaluation of several automated speech recognition systems confirmed previous research that has suggested that those systems have more difficulty in recognising the speech of older adults (Werner et al, 2019).…”
Section: Age Bias In Aisupporting
confidence: 74%
See 1 more Smart Citation
“…However, age-related physical changes may alter speech production and limit the effectiveness of ASR systems for older individuals. Evaluation of several automated speech recognition systems confirmed previous research that has suggested that those systems have more difficulty in recognising the speech of older adults (Werner et al, 2019).…”
Section: Age Bias In Aisupporting
confidence: 74%
“…Recent analysis shows also that age-biased samples and biased tools used for constructing algorithms tend to exclude the habits, interests and values of older people what contributes to strengthening already existing structural ageism (Rosales and Fernández-Ardèvol, 2019 ). Studies of age bias in machine learning are still rare, but persistently show that age bias exists in sentiment analysis models (Díaz et al, 2018 ), face recognition systems using advanced deep learning techniques (Meade et al, 2021 ), in emotion recognition systems (Kim et al, 2021 ), as well as in speech recognition systems (Werner et al, 2019 ).…”
Section: Age Bias In Aimentioning
confidence: 99%
“…Several implications for speech assistants, like longer pauses between words, are mentioned, which should be considered in future systems. Werner et al [34] also indicate, that there might be agerelated differences in the word error rates of ASR systems, which would need to be considered when building ASR models.…”
Section: Resultsmentioning
confidence: 99%
“…This could be related to the age of the persons in this group; since residents are the group with the highest average age, they are more likely to suffer from speech problems. 24 …”
Section: Discussionmentioning
confidence: 99%